A Stereoselective, Base‐free, Palladium‐Catalyzed Heck Coupling Between 3‐halo‐1, 4‐Naphthoquinones and Vinyl‐1H‐1, 2, 3‐Triazoles. Issue 24 (23rd June 2022) - Costa, Dora C. S.; da S. M. Forezi, Luana; Lessa, Milena D.; Delarmelina, Maicon; Matuck, Beatriz V. A.; Freitas, Maria Clara R.; Ferreira, Vitor F.; de C. Resende, Jackson A. L.; de M. Carneiro, José Walkimar; de C. da Silva, Fernando
Abstract: A stereoselective, base‐free Heck coupling between 1, 4‐naphthoquinone and 1 H ‐1, 2, 3‐triazole derivatives was reported for the first time. This study shows that depending on the 1, 4‐naphthoquinone, the use of an additional base is unnecessary to produce the naphthoquinone‐triazole conjugates. This is also the first example of a Heck coupling of these two cores without using a base as an additive. In this work, sixteen new naphthoquinone‐triazole hybrids were stereoselectively synthetized in good to excellent yields. The reaction mechanism was discussed based on DFT CAM−B3LYP calculations. The first step is the coordination of the arene to the palladium catalyst to form a palladacycle intermediate. After reorganization in this intermediate, the double bond in the arene is restored to proceed with the coupling step and formation of the C−C bond in the rate determining step. The Kozuchi‐Shaik span model was employed to rationalize substituent effects. Abstract : A stereoselective, base‐free Heck coupling between 1, 4‐naphthoquinone and 1 H ‐1, 2, 3‐triazole derivatives was reported for the first time. Sixteen new naphthoquinone‐triazole hybrids were stereoselectively synthetized in good to excellent yields, and the reaction mechanism was intensely discussed by computational studies. This study opens a new way to synthesize potential bioactive compounds.